NEON BOY: A HISTORICAL VIEW ON THE NEW MASCULINITY REPRESENTATIONS - Calori de Lion, Antonio Ricardo [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias Humanas & Sociais, 2019)
This paper aims to reflect on masculinities in the Brazilian northeastern context, taking into consideration the new model of masculinity represented in the movie Neon Bull (2015), by the character Iremar (Juliano Cazarre). Thus, we search according to the bibliographical discussion on the subject - mainly from Joao Silverio Trevisan's contribution about the crisis of the maleness - to (re)think performativities created over the male body and the historical relation between new standards and the historical construction of the gender relations discussed here by Durval Muniz de Albuquerque Junior's production about the invention of the northeastern men virility according to violent and rural archetypes.
Keywords: Neon Bull; masculinities; gender relations history; crisis of masculinity